Multimorbidity of hidradenitis suppurativa: a cross-sectional population-based study of its associated comorbidities - Almenara-Blasco, Manuel; Gracia-Cazaña, Tamara; Poblador-Plou, Beatriz; Laguna-Berna, Clara; Navarro-Bielsa, Alba; Moreno-Juste, Aida; Gimeno-Miguel, Antonio; Gilaberte, Yolanda (Frontiers in Medicine, 2025)
BackgroundHidradenitis suppurativa (HS) is a chronic, inflammatory skin disorder associated with significant physical and psychological burden. While individual comorbidities have been described in prior studies, a comprehensive analysis of all chronic conditions associated with HS in a large population-based cohort is lacking.ObjectivesTo determine the prevalence of hidradenitis suppurativa in a large-scale, population-based study, to describe its comorbidities, and to analyze which diseases are associated with the presence of hidradenitis.MethodsRetrospective cross-sectional observational study based on the clinical information contained in the electronic health records from the individuals of the EpiChron Cohort (Aragón, Spain) with a diagnosis of hidradenitis suppurativa (1,003 individuals from all ages and sexes) in 2019. We analyzed the prevalence of chronic comorbidities and used logistic regression models adjusted for age, sex and comorbidities to calculate the likelihood of occurrence of each of the comorbidities with a prevalence ≥1% based on the presence of hidradenitis. We used a cut-off point for statistical significance of p-value < 0.05.ResultsThe prevalence of hidradenitis suppurativa was 0.10%, and it was more prevalent in women (0.12% vs. 0.08%). The most frequent chronic comorbidities were disorders of lipid metabolism (27.8%), hypertension (19.7%), and anxiety disorders (18.7%). The conditions most associated with hidradenitis were (odds ratio; 95% confidence interval) skin and subcutaneous tissue infections (3.32; 2.56–4.30), diseases of white blood cells (2.11; 1.44–3.07), and schizophrenia and other psychotic disorders (2.17; 1.16–4.06), among others.ConclusionHS is associated with a high burden of multimorbidity, encompassing metabolic, neuropsychiatric, musculoskeletal, and infectious conditions. These findings underscore the need for integrated and multidisciplinary management strategies. Further longitudinal research is warranted to explore causal relationships and improve clinical outcomes.